Therapeutic plasma exchange in neurological disorders: Experience from a tertiary neuroscience centre. (December 2019) - Das, Joyutpal; Chauhan, Vanisha D.; Mills, Daniel; Johal, Nicholas J.; Tan, Maevis; Matthews, Rachael; Keh, Ryan; Lilleker, James B.; Gosal, David; Sharaf, Nazar
Abstract: Therapeutic plasma exchange (TPE) involves the extracorporeal separation of plasma from the cellular components of blood with replacement fluid, such as human albumin or fresh frozen plasma. A number of studies across the world revealed that more than one third of TPE procedures were performed for neurological disorders. Myasthenia gravis (MG), Guillain-Barré syndrome (GBS) and chronic inflammatory demyelinating polyneuropathy (CIDP) were the most frequently cited indications for TPE, followed by multiple sclerosis (MS). However, treatments of these conditions have evolved over the years and it is likely that this has impacted on clinical practice. Here we present our experience of using TPE to treat neurological disorders. We reviewed the medical records of all 63 patients who received 349 procedures over 70 therapeutic cycles between 2012 and 2015 in a tertiary neurology centre. In total only 2 patients with GBS and MG were treated with TPE. The commonest indication was voltage gated potassium channel (VGKC) complex antibody associated disorders followed by CIDP and MS. There were 11 patients with limbic encephalitis. Nine of them had antibodies against VGKC complex and two had N-methyl-D-aspartate (NMDA) receptor antibodies. Sixty four percent of patients with limbic encephalitis and overall 78% of patients responded to TPE. The complication rate associated with this procedure was 8.6 per 100 therapeutic cycle. There was no treatment related mortality. We observed a change in indications of TPE compared to historical studies. It was less frequently used to treated GBS and MG. It was found to be safe and effective.